Performance Enhancement Of PesZif-L Mixed Matrix Membrane Using Ionic Liquid For Co2N2 Separation - Saufi, Muhammad Amirul Asraf Mohd (Universiti Sains Malaysia, 2022)
Mixed matrix membrane (MMM) popularity has been increasing in research field recently due to promising gas separation performance that offered by the characteristic of inorganic filler and the durability to heat, chemical and mechanical that inherited from polymeric membrane. However, the issue that has been encountered by MMM is the poor compatibility between the organic particles and the polymer that causing interfacial defects that disrupt the gas separation process. In this study, MMM that consist of ZIF-L as the inorganic filler and polyethersulfone (PES) was fabricated via thermal induced phase separation (TIPS) method. The loading of ZIF-L was varied from 0.25 to 1.0 wt.% to study the effect of ZIF-L loading on the characteristic of the MMMs and its gas separation performance. Increasing the ZIF-L loading has enhanced the CO2 permeance but it reduced the CO2/N2 selectivity as it compared to intrinsic attributes of PES. The ZIF-L incorporation has resulting in voids formation between the polymer and filler as shown by the electron microscopy images. Ionic liquid (IL) which selective towards CO2 was used in this study to modify the MMM by sealing the interfacial void between the membrane and the filler. Two methods of modification were tested. They are pre-modification of ZIF-L and post-modification of PES/ZIF-L MMM. Results obtained shows that pre-modification has successfully sealed the polymer/filler interfacial void compared to post-modification. The comparison study revealed that the pre-modification has successfully enhanced PES/ZIF-L membrane’s performance as the membrane shown a promising attribute that is closest one to the Robeson upperbound curved 2008 compared to other membranes that are also fabricated in this study. PES/ZIF-L with 0.75 wt.% ZIF-L loading, CO2 permeance and CO2/N2 selectivity has been enhanced up to 0.721 GPU and 37.283 respectively after pre-modification.